Heterogeneous vancomycin-intermediate Staphylococcus aureus (HVISA) at a tertiary hospital in Malaysia - Hamasalih, Bakhtiyar Mahmood; Neoh, Hui-min; Rosni Ibrahim,; Lailatul Akmar Mat Nor,; Tengku Zetty Maztura Tengku Jamaluddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Methicillin-resistant Staphylococcus aureus remains a global problem. The emergence of reduced susceptibility to Vancomycin in MRSA strains, leads to treatment failure and prolonged hospital stay. Therefore, we aimed to determine the strains with reduced susceptibility among MRSA clinical isolates. S. aureus isolates were collected from identified clinical samples. Antibiotic susceptibility was tested using the Kirby-Bauer method. MRSA strains were confirmed using PCR for mecA gene and subjected to the Epsilometer test (Etest®) for determination of Vancomycin minimum inhibitory concentration (MIC). Isolates with intermediate or reduced susceptibility were subjected to broth microdilution (BMD) and further confirmed by population analysis-area under curve (PAP-AUC) testing. Disc diffusion tests showed that all isolates (n = 105; 100%) were susceptible to Rifampicin, followed by Trimethoprim/Sulfamethoxazole. Meanwhile, a high resistance rate was demonstrated against Penicillin (n = 93; 88.6%). Among all isolates, only 26.0% (n = 27) were MRSA. According to the Vancomycin MIC value by Etest®, only two strains (A3, A106) had intermediate susceptibility, and one strain (A30) had reduced susceptibility to Vancomycin (MIC 3 μg/mL). No susceptibility to Vancomycin was identified among strains using the BMD method. According to the PAP-AUC method, it was confirmed that strain A3 was a heterogeneous VISA strain. Vancomycin Etest®, is a reliable screening test for VISA detection. Vancomycin BMD result was not in agreement with the Vancomycin Etest® result. PAP-AUC, the gold standard test used to detect Vancomycin resistance, should be conducted whenever possible for further confirmation and epidemiological record.